Towards a biological definition of ARDS: are treatable traits the solution? - Bos, Lieuwe D. J.; Laffey, John G.; Ware, Lorraine B.; Heijnen, Nanon F. L.; Sinha, Pratik; Patel, Brijesh; Jabaudon, Matthieu; Bastarache, Julie A.; McAuley, Daniel F.; Summers, Charlotte; Calfee, Carolyn S.; Shankar-Hari, Manu (Intensive care medicine experimental, 2022)
The pathophysiology of acute respiratory distress syndrome (ARDS) includes the accumulation of protein-rich pulmonary edema in the air spaces and interstitial areas of the lung, variable degrees of epithelial injury, variable degrees of endothelial barrier disruption, transmigration of leukocytes, alongside impaired fluid and ion clearance. These pathophysiological features are different between patients contributing to substantial biological heterogeneity. In this context, it is perhaps unsurprising that a wide range of pharmacological interventions targeting these pathophysiological processes have failed to improve patient outcomes. In this manuscript, our goal is to provide a narrative summary of the potential methods to capture the underlying biological heterogeneity of ARDS and discuss how this information could inform future ARDS redefinitions. We discuss what biological tests are available to identify patients with any of the following predominant biological patterns: (1) epithelial and/or endothelial injury, (2) protein rich pulmonary edema and (3) systemic or within lung inflammatory responses.